Arguing against the proposed definition changes of PD. Issue 11 (5th August 2016) - Boeve, Bradley F.; Dickson, Dennis W.; Duda, John E.; Ferman, Tanis J.; Galasko, Douglas R.; Galvin, James E.; Goldman, Jennifer G.; Growdon, John H.; Hurtig, Howard I.; Kaufer, Daniel I.; Kantarci, Kejal; Leverenz, James B.; et al.
ABSTRACT: As members of the Lewy Body Dementia Association Scientific Advisory Council, we aim to address some of the issues raised in the article titled "Time to Redefine PD? Introductory Statement of the MDS Task Force on the Definition of Parkinson's Disease." In particular, we suggest that the 1‐year rule distinguishing Parkinson's disease dementia from dementia with Lewy bodies is worth maintaining because it serves an important purpose in clinical practice and clinical and basic science research and when helping the lay community understand the complexity of these different clinical phenotypes. Furthermore, we believe that adding an additional diagnostic label, "PD (dementia with Lewy bodies subtype), " will confuse rather than clarify the distinction between dementia with Lewy bodies and PD or PD dementia, and will not improve management or expedite therapeutic development. We present arguments supporting our contentions. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.